Immune checkpoint inhibitors in advanced nasopharyngeal carcinoma: Beyond an era of chemoradiation?. Issue 8 (28th January 2020) - Masterson, Liam; Howard, James; Gonzalez‐Cruz, Jazmina; Jackson, Christopher; Barnett, Catherine; Overton, Lewis; Liu, Howard; Ladwa, Rahul; Simpson, Fiona; McGrath, Margie; Wallwork, Ben; Jones, Terry; et al.
Abstract : Now is an exciting era of development in immunotherapy checkpoint inhibitors and their effect on the treatment of NPC. While the general prognosis of R/M disease is poor, immunotherapy offers some promise in a malignancy associated with EBV and characterized by a peritumoural immune infiltrate. Our study aims to review past and on‐going clinical trials of monoclonal antibody therapies against the checkpoint inhibitors (e.g. PD1 and CTLA‐4), in R/M NPC. All randomized and nonrandomized controlled trials involving immune checkpoint inhibitor interventions for treatment of NPC were included in the study. We utilized a validated "risk of bias" tool to assess study quality. Four separate Phase I–II trials report the potential of PD1 inhibitor treatment for patients with NPC. Within the observed groups, camrelizumab combined with chemotherapy achieved an objective response in 91% of patients as first‐line treatment for metastatic NPC (PFS 68% at 1‐year) but this was associated with a high rate of grade >3 adverse events (87%; CTCAE version 4.03). The remaining three studies focused on recurrent NPC disease in patients who had received at least one line of prior chemotherapy. Within this group, camrelizumab monotherapy achieved an objective response in 34% of patients (PFS 27% at 1‐year; range across all three studies 20.5–34%). No NPC trial has yet reported on specific outcomes for non‐PD1 checkpoint inhibitors but 11 on‐going studies include alternative targets (e.g. PD‐L1/CTLA‐4) as combination or monotherapy treatments. In considering checkpoint immunotherapies for NPC, initial results show promise for anti‐PD1 interventions. Further phase I–III trials are in progress to clarify clinical outcomes, fully determine safety profiles, and optimize drug combinations and administration schedules. What's new?: Given limited recent advances in chemotherapeutic regimens, there is an urgent need to develop targeted therapies for metastatic nasopharyngeal carcinoma (NPC) that reduce toxicity and improve survival benefit. This review of clinical trials with monoclonal antibodies against checkpoint inhibitors shows that anti‐PD1 is a potential treatment option for patients with recurrent/metastatic NPC. Camrelizumab combination therapy achieved the best clinical outcome, but was associated with a high rate of serious adverse events. As immunotherapy gets incorporated into standard treatments, issues of optimal combinations with targeting agents and immune adjuvants and sequence with chemotherapy and radiation therapy will need to be addressed.